P48 Haematopoietic but not mesenchymal stem cells contribute to the stromal microenvironment in cholangiocarcinoma and do not transdifferentiate into malignant bile ducts. (16th November 2010) - Robson, A; Samuel, K; Pellicoro, A; Iredale, J; Forbes, S
Abstract : Aim: Cholangiocarcinoma (CC) is characterised by a pronounced inflammatory stroma consisting of tumour associated myofibroblasts, macrophages, immune cells and a modified extracellular matrix. Furthermore, in animal models of gastric cancer, reports have suggested that mesenchymal stem cells may contribute to the epithelial compartment of malignant tumours. The treatment options for CC are very limited. Therefore, an understanding of the source of tumour-associated cells in CC will inform therapy in the future. Method: The matrix and cellular composition of the tumour niche was studied in humans and the thioacetamide (TAA) rat model of CC over 10 months. To investigate the cellular origin of the tumour and associated stroma, reconstituted wild type recipients of GFP+ bone marrow were administered TAA. Extra-hepatic derivation of cells was studied using dual immunoflourescence (GFP and CK19 (biliary epithelium), SMA (myofibroblasts), ED1, ED2 (macrophages) and MPO (neutrophils).) Persistent expression of GFP+ BM in control transplanted animals was confirmed by qPCR for Y-chromosome genomic DNA. Flow cytometry of blood, spleen and BM was performed to investigate GFP+ donor reconstitution of the haematopoietic compartment in recipient rats. BM of transplanted animals was cultured in mesenchymal stem cell (MSC) selective media and flow cytometry analysis for co-expression of stro-1 (a marker of MSC) and GFP was performed. Results: In human and rat tissue a laminin rich extracellular matrix ensheathed neoplastic cholangiocytes. The tumour cellular microenvironment comprised of myofibroblasts, migratory macrophages (CD68+) and immune cells. In transplanted rats, GFP+ expression was persistent throughout the study period and chimerism was confirmed in BM, spleen and blood. GFP+ reconstitution of the haematopoietic and mesenchymal stem cell compartments was identified. Expression of stro1+GFP+ cultured cells was similar in transplanted animals and control GFP+ animals. In tumours, macrophages (ED1, ED2) and neutrophils (MPO) were overwhelmingly GFP+, whereas myofibroblasts (SMA) did not express GFP. Additionally, benign and malignant bile ducts were GFP negative. Conclusion: A stereotypical niche forms around cholangiocarcinoma in developing and malignant lesions. The TAA rat model provides close correlation to human intrahepatic lesions with formation of a pronounced tumour microenvironment. We found no evidence of a BM-derived stem cell contribution to the epithelial component of cholangiocarcinoma. The haematopoietic but not the mesenchymal components of the tumour stroma were of BM origin.